PENGARUH PEMBELAJARAN AKIDAH AKHLAK TERHADAP KECERDASAN SOSIAL SISWA KELAS XI DI MAN 1 KOTA BUKITTINGGI - Sri Inayati; Salmiwati Salmiwati; Junaidi Junaidi; Januar Januar (CV. ADIBA AISHA AMIRA, 2023)
Aqidah Akhlak learning aims to provide basic skills to students regarding Islamic beliefs to develop religious life so that they become Muslims who believe and fear Allah SWT, and have noble character. But in reality there are still some students who are lacking in the application of their knowledge. Even though in the learning process they have been taught about adab, commendable morals and also despicable morals so that with this material students should be able to behave like a good student. This study aims to determine how much influence the learning of aqidah morals has on the social intelligence of class XI students at MAN 1 Bukittinggi City. This research is a quantitative research by distributing questionnaires to students who are members of the sample with a Likert scale. Data analysis techniques using statistics with calculations to answer the problem formulation and perform calculations to test the hypotheses that have been proposed with the help of the SPSS 26 program. The results of the study revealed that there was an influence between learning aqidah morals on students' social intelligence. The results of the hypothesis test show that there is a significant level of 0.003 <0.05, which means that the X variable has an effect on the Y variable. The magnitude of the effect can be seen from Rsquare, which is 0.235, which can be interpreted as having an effect of 23.5%.